EPI at 7T : functional imaging and off-resonance correction techniques - Harmer, Jack (2013)
The work presented in this thesis describes the development and implementation of a number of ideas and methods that allow fMRI to be carried out using echo-planar imaging at ultra high field strength, despite the significant problems associated with this. In the first study, EPI is used to probe how the gradient echo (GE) and spin echo (SE) BOLD responses relate to the underlying neurological processes, whilst the brain is in both its active and resting states. These finding show that SE BOLD contrast is harder to detect but less localised to areas around large draining veins than GE BOLD contrast and thus potentially more localised to sites that represent true functional areas of activation. The second study describes how dynamic delta B0 mapping can be performed during fMRI experiments with a hyperoxic challenge in order to assess the magnitude and extent of delta B0 effects that arise due to susceptibility differences between air and tissue. Developing on this, this work describes the steps involved in the design and implementation of a dual echo GE/SE EPI sequence and how it can be used to enable off-resonance effects, such as image distortion and signal concentration/dilution, to be corrected on a dynamic basis for, simultaneously acquired, GE and SE data. The final study demonstrates how such a sequence can be used to detect resting state networks. Showing that the correspondingly low temporal separation of the GE and SE data allows GE and SE BOLD contrast mechanisms to be compared in a number of novels ways in different resting state networks.